2010
DOI: 10.1001/jama.2010.1633
|View full text |Cite
|
Sign up to set email alerts
|

Automated Surveillance to Detect Postprocedure Safety Signals of Approved Cardiovascular Devices

Abstract: ONITORING THE SAFETY OF approved medical productsisofvitalpublichealth importance, given that in clinical practice such medical products are often used in numbers far greater and in patient populations more diverse than when studied in premarket evaluations and clinical trials. [1][2][3][4][5][6] Within the broad range of medical products, implantable medical devices represent high-risk products that are uniquely challenging to monitor because there is little consensus regarding the most appropriate methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
(53 reference statements)
0
46
0
Order By: Relevance
“…9,22,23 To continue matching to the nearest propensity score as the monthly data sets grew, at the end of each month's analysis all matches were released, and a completely new matching was conducted at the next month's analysis. Control subjects were not allowed to match to more than 1 exposure.…”
Section: Risk Adjustment Through Propensity Matchingmentioning
confidence: 99%
See 2 more Smart Citations
“…9,22,23 To continue matching to the nearest propensity score as the monthly data sets grew, at the end of each month's analysis all matches were released, and a completely new matching was conducted at the next month's analysis. Control subjects were not allowed to match to more than 1 exposure.…”
Section: Risk Adjustment Through Propensity Matchingmentioning
confidence: 99%
“…The feasibility of performing computerized automated prospective surveillance of large clinical outcomes registries was demonstrated by Resnic et al, 9 who applied DELTA to a database of Ͼ74 000 interventional coronary procedures contained in the Massachusetts angioplasty registry. Using a variety of statistical methods, including propensity score matching, DELTA triggered a sustained alert for a specific drug-eluting stent because patients receiving this particular model were having a higher rate of periprocedural myocardial infarction than matched control patients treated with another market-released drug-eluting stent.…”
Section: Hauser Et Al Early Detection Tool 193mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the specific findings, the study by Resnic et al 5 represents an important advance in surveillance methodology. It principally supports the feasibility of automated monitoring for device safety signals.…”
mentioning
confidence: 94%
“…It has already been demonstrated that automated safety surveillance of clinical registries for approved cardiovascular devices can provide early warnings regarding the safety of approved cardiovascular devices in clinical practice. 9 It is our belief that similar to what was carried out in the BICIS-1 study, long-term follow-up using a death index would allow safety information such as mortality to be collected prospectively without holding up an approval process. This would be of particular value for high-risk interventions where long-term mortality data are not usually available.…”
Section: Vavalle and Ohman Left Ventricular Support Systems For High-mentioning
confidence: 99%